Content of Volume 19 Issue 1 June 2023 - Interdental Jurnal Kedokteran Gigi (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Content of Volume 19 Issue 1 June 2023 SUB-ACUTE TOXICITY TEST OF RED GINGER EXTRACT (Zingiber officinale var. Rubrum) ON MICE (Mus musculus) Putu Sulistiawati Dewi, Mochammad Taha Ma’ruf 1-5 THE EFFECT OF SMOKING HABITS ON THE OCCURRENCE OF BRUXISM: A RAPID REVIEW Prida Lani Debora P, Rasmi Rikmasari, Seto Pramudita 6-10 TREATMENT OF HERPES ASSOCIATED ERYTHEMA MULTIFORME (HAEM) Raziv Ganesha, Rina Kartika Sari 11-16 CORRELATION OF MOUTH BREATHING HABITS TO DENTAL MALOCCLUSIONS Ketut Virtika Ayu, I Dewa Gede Budijanana, Norman Hidajah, Surwandi Walianto 17-21 EARLY DETECTION OF VERRUCOUS CARCINOMA USING METHYLENE BLUE STAINING IN SUSPECTED LEUKOPLAKIA LESION: A CASE REPORT Rina Kartika Sari, Raziv Ganesha, Esti Kurniawati 22-28 RELATIONSHIP BETWEEN THE ANGLE OF INCLINATION OF THE MAXIMUM INCLINATION TO THE SOFT TISSUE OF THE FACIAL IN BALINESE WOMEN USING THE HOLDAWAY METHOD Norman Hidajah, Dwis Syahrul, Ketut Virtika Ayu 29-33 GEL GEL EXTRACTION OF EARTHWORMS (Lumbricus rubellus) TO THE NUMBER OF FIBROBAL CELLS IN MALE WISTAR RATS (Rattus norvegiccus) GINGIVAL WOUND HEALING Ni Wayan Arni Sardi, Ni Luh Putu Sri Maryuni Adnyasari, Ni Putu Ratih Berliana Ekasari 34-42 THE USE OF CHLORHEXIDINE MOUTHWORKS CAN REDUCE THE ACCUMULATION OF DENTAL PLAK IN USERS OF FIXED ORTHODONTIC DEVICES Dwis Syahrul, Surwandi Walianto, Priscilla Sonia Suwongto 43-48 EFFECTIVENESS OF RED BITES FRUIT (Beta vulgaris) AS A MOUTH MOUTH TO REDUCE HALITOSIS I Gusti Ngurah Putra Dermawan, Intan Kemala Dewi, Fritz Gerald Dharma Tedjamartono 49-54 PLAQUE CONTROL IN PERIODONTAL DISEASE Ni Luh Putu Sri Maryuni Adnyasari, Dwis Syahriel , I.G.A Dewi Haryani 55-61 ERUPTION CYST OVERLYING THE CROWN OF UPPER RIGHT FIRST PREMOLAR: A CASE REPORT Wayan Sutresna Yasa, Kirana Guspiari, I Made Hendra Cahyadita Nusantara Putra 62-66 LD50 ACUTE TOXICITY TEST OF GREEN GRASS JELLY (Cyclea barbata Miers) LEAF EXTRACT AGAINST MICE (Mus musculus L.) Hendri Poernomo, Mochammad Taha Ma’ruf, Ari Sucitra Dewi 67-73